FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU MEROKOK SISWA/SISWI SEKOLAH MENENGAH KEJURUAN YAYASAN PENDIDIKAN INDONESIA MEMBANGUN NAMORAMBE TAHUN 2014 - anovy yuwinda harahap; Yusniwarti Yusad; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Based on data the World Health Organization (WHO) explain that one of the 10 deaths in adults are caused by smoking. Indonesia is the 3rd highests number of smoker in the world.Adolescent victims of exploitation largest cigarette industry. Adolescence identical as a free human. Therefore teenagers always do all the desired activities. Many teenagers who like to do things like smoking prohibited. The research aims to determine the factors that influence smoking behavior of students. Type of research is descriptive analytic survey design Cross Sectional Study. Population in the research were 63 students and all of sample. Result of data analysis using chi-square and of the 8 existing variables obtained 6 related variables is sex ρ=0,0001 , knowledge ρ=0,009, age ρ=0,099, attitude ρ=0,008, advertising ρ=0,009 and peer group ρ=0,0001.Based on multivariate analysis of the variables that most influence is variable peer group on smoking behavior with logistic regression test value of Ex (B)=41,600, and of 63 students there are 25 who smoke, 24 sex male and 4 female. Expected to cooperate with the school to parent to provide information about the factors that influencesmoking behavior, especially peer group factor (enviroment) that play a role in influencing students behavior and for adolescents should be more careful in getting along in daily life so as not to be affected by adverse behavior. Key word : Smoking behavior, Peer group, sex